Whipping phytoliths into shape (and size). A Commentary on: ‘Inter- and intraspecific variation in grass phytolith shape and size: a geometric morphometrics perspective’ - Strömberg, Caroline A E (Ann Bot, 2020)
This article comments on: Kristýna Hošková, Adéla Pokorná, Jiří Neustupa and Petr Pokorný, Inter- and intraspecific variation in grass phytolith shape and size: a geometric morphometrics perspective, Annals of Botany, Volume 127, Issue 2, 01 February 2021, Pages 191–201, https://doi.org/10.1093/aob/mcaa102